Influenza activity in Portugal - 2010/2011 season - Gonçalves, Paulo (2012)
Influenza activity in Portugal has been monitored since 1953 at the National Institute of Health. Clinical and virological data is analysed and ILI incidence rates are estimated weekly. Information is forwarded to National Health Authorities, contributing for the management of the disease. Since the 2009/2010 influenza pandemic, the National Influenza Surveillance Programme collects and integrates information generated through 3 surveillance structures, the Network of Sentinel Medical Practitioners (since 1990), the Network of Emergency Units (since 1999), and the Network of Laboratories for Influenza A(H1N1)2009 Diagnosis (since 2009). Together they provide a clearer picture of the influenza activity in the Country. Preliminary data (up to W18/2011) suggests that during the 2010/2011 winter season the influenza activity was moderate (max. 109.7 ILI cases/105 inhabitants on week 1/2011, provisory estimate), with an epidemic period of 11 weeks (W50/2010 to W8/2011). Influenza viruses type B/Vic were predominant at the beginning of the season but were gradually replaced by A(H1)2009 viruses, which became dominant from the middle of the season (W1/2011) onwards. Both types were antigenic and genetically similar to the vaccine strains. Type A(H3) and B/Yam viruses were also detected. Although the majority of ILI cases (53.7%) were from adults (15-44 years), the highest proportion (70.3%) of influenza cases was observed in children (5-14 years). Information on influenza vaccination with the 2010/2011 trivalent vaccine was available for 83.4% of cases. From those vaccinated (11.7%), the highest proportion (39.4%) of individuals were in the >65 years age group (7.1% were children up to 14 years) and 28.3% were positive for influenza. In terms of clinical presentation, fever and cough were the symptoms with the highest association with a positive laboratory diagnosis [OR 4.7 (2.7-8.1) and 3.9 (2.4-6.5), respectively], when all symptoms (according to ICHPPC-II definition) are considered independently. However, when influenza-type is considered, the odds ratio for fever is lower for type A than for type B [OR 2.9 (1.5-5.5) and 3.9 (1.7-9.0), respectively), and for cough is higher for type A than for type B [OR 4.9 (2.3-10.2) and 1.7 (0.9-3.0), respectively]. As expected, the pandemic A(H1)2009 virus has adopted a seasonal behaviour during the 2010/2011 season, co-circulating with influenza B. Influenza activity and clinical presentation were similar to previous seasons.